Communication—Enhanced Dielectric Constant of Polymer Composites via Regulating Thermal Reduction Treatment Time of Graphene Oxide. (10th January 2022) - Liu, Hui; Ma, Lili; Yan, Yichao; Lei, Qingquan; Xin, Meng
Abstract : The addition of graphene can change the distribution of conductive pathways in the polymer composites and further affect the dielectric properties. In this work, a facile and environmentally friendly method was proposed to enhance dielectric properties by manipulating the reduction extent of reduced graphene oxide (RGO) in polyvinylidene fluoride (PVDF) matrix just through altering the thermal reduction treatment time. Measurement results showed that the electrical percolation occurred as thermal reduction treatment time increased and the conduction mechanism changed into approximate free electron model. RGO/PVDF composites with tailorable dielectric properties were realized with a low filler loading level.